Analisis Hadis Dua Belas Khalifah antara Sunni dan Syiah - Ma’ruf, Abdullah (AL-BURHAN, 2023)
Among the significant theological differences between Sunnis and Shias is the obligation to follow the Imams. The number of these Imams is twelve, based on a hadith of the Prophet Muhammad (PBUH). This hadith is crucial as it serves as the foundation of the Shia creed in affirming the existence of twelve Imams. Conversely, Sunnis are also required to address this hadith, as it is found in several Sunni hadith collections.This study is categorized as library research, utilizing qualitative and comparative methods. The Hadith of the Twelve Caliphs is considered authentic by both Sunni and Shia scholars. Shia scholars interpret the hadith to mean that every Muslim must believe in the twelve Imams they recognize. However, Sunni scholars have differing opinions, as the number of caliphs succeeding the Prophet exceeds twelve. Interpreting this hadith as referring to Shia Imams is problematic, as it conflicts with historical facts.The term “caliph” here cannot be limited to spiritual or religious authority but must also encompass leadership of the Islamic state. Meanwhile, the twelve Imams in Shia tradition, except for Ali ibn Abi Talib, had no direct role in advancing Islam.Keywords: Twelve Caliphs, imam, Shia, Sunni, hadith.